Modification of Agro-wastes Reinforced onto the PET Fabric for Decolorisation of Palm Oil Mill Effluent - Suradi, Siti Samahani; Kamaruzaman, Muhammad Zarif Hazim; Mohd Dali, Muhammad Izz Zakwan; Abu Bakar Sidik, Dilaeleyana; Bujang, Hazirah; Abdullah, Nurmina; Hairom, Nur Hanis Hayati; Dzinun, Hazlini; Rosley, Rozainita (semarak ilmu, 2024)
The abundance of agricultural wastes from various industrialized processes has become one of the significant contributors to water pollution, particularly in the color of effluents from industrial-based palm oil mills. Inventively, this research focused on three different agro-wastes: pineapple leaves (PL), rice straw (RS), and empty fruit bunch (EFB) reinforced onto PET fabric composite and its decolorization performances by using palm oil mill final effluent discharged (POME-FED). The calcinated agro wastes/polyvinylidene fluoride (PVDF) reinforced onto the polyethylene terephthalate (PET) fabrics were prepared by using the dip-coating technique and characterized via Scanning Electron Microscopy (SEM-EDS), spectroscopy (FTIR-ATR), turbidity and color of POME-FED. It was found that the calcinated PL/PVDF/Fabric displayed the best performance in the turbidity and decolorization by 12.02 NTU, 760 ADMI, and ~60% color removal efficiency as compared with raw POME-FED (~1800 ADMI). Nevertheless, the decolorization efficiencies of RS/PVDF/Fabric and EFB/PVDF/Fabric had increased by ~37 % and ~49 %, respectively. It shows that the formation of a reinforcing layer on the PET fabric surface has improved the transparency of POMEFED. The SEM micrographs and the change of peaks at regions 1650 cm-1, 1450 cm-1, 1210 cm-1, and 990 cm-1 in composites' spectroscopies demonstrate the different patterns of these calcinated samples are various patterns that impart the strength of the composite fabric surface functionality and hydrophobicity. The reduction of the color value of effluent showed the hydrophobicity of the integrated palm oil waste coated with PET, which enables to trap of the particles in the effluent, thus this composite has potential use in the filtration of water treatment.